Implementasi Smart Farming Dengan Sistem Monitoring Kelembaban Dan Suhu Pada Tanaman Peppermint Berbasis Internet Of Things - Muhammad Najamuddin Dwi Miharja; Tyo Repsi Harta Sanjaya (Teknik Informatika, Universitas Pelita Bangsa, 2022)
Technological developments in agriculture are increasingly advanced. all industries are competing to use the technology that characterizes the industrial revolution. To more easily understand Industry 4.0, the key is an internet-based network. One of them is smart farming. namely the use of platforms that are connected to technological devices. The mint plant comes from the European continent. This plant can grow anywhere such as Europe, Asia, Africa, Australia and North America. This plant can grow at an altitude of 100 to 900 m above sea level with a temperature of 20˚C – 30˚C, humidity 80-95% and full light intensity. In the research, the IOT bolting for temperature and humidity control, the results of this monitoring system proved that the sensor error rate was very small, which was 4%. Keywords Internet Of things(IOT), Smart Farming, hydroponics.